Peran Guru PAI dalam Pembentukan Literasi Keagamaan Siswa pada Era Society 5.0 di Kelas VI SD N Kaliwlingi 01 - Erin Rizka Amaliyah; Alfina Damayanti; Fadia Vera Aulia; Nahdia Izzatul Ulya; Ishlah Seillariski (CV. Alim's Publishing, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in developing students’ religious literacy in the Society 5.0 era at SDN Kaliwlingi 01, identify the supporting and inhibiting factors, and describe teachers’ strategies in integrating technology with religious values. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers, the principal, sixth-grade homeroom teachers, sixth-grade students, and parents. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that PAI teachers play significant roles as educators, mentors, facilitators, and role models in fostering students’ religious literacy through religious habituation, worship practices, religious instruction, and the utilization of technology in learning activities. Supporting factors include the school’s religious culture, technology-based learning media, and collaboration among school members. Meanwhile, inhibiting factors include limited participation of some students in religious education outside school, inadequate technological facilities, and uncontrolled gadget use. The strategies implemented by teachers involve the use of digital media such as learning videos, PowerPoint presentations, the internet, and Smart TVs integrated with direct religious practices. The study concludes that the integration of technology and religious values effectively enhances students’ religious literacy while maintaining the development of religious character in the Society 5.0 era.